MORPHOBIOLOGY AND MEDICINAL PROPERTIES OF SUNBERRY (SOLAUM RETROFLEXUM L.) (American Journal of Interdisciplinary Research and Development, 2022)
The article contains valuable information about the morphobiology and medicinal properties of the sunberry (Solaum retroflexum L.). Also, the substances found in the sunberry plant and their amount were written in the article.